BrachyView: development of an algorithm for real-time automatic LDR brachytherapy seed detection. (4th November 2020) - Brennen, T; Galli, L; Cutajar, D L; Alnaghy, S; Bucci, J; Bece, A; Enari, K; Favoino, M; Carriero, M; Tartaglia, M; Archer, J; Lerch, M; et al.
Abstract: BrachyView is a novel in-body imaging system developed to provide real-time intraoperative dosimetry for low dose rate prostate brachytherapy treatments. Seed positions can be reconstructed after in-vivo implantation using a high-resolution pinhole gamma camera inserted into the patient rectum. The obtained data is a set of 2D projections of the seeds on the image plane. The 3D reconstruction algorithm requires the identification of the seed's centre of mass. This work presents the development and techniques adopted to build an algorithm that provides the means for fully automatic seed centre of mass identification and 3D position reconstruction for real-time applications. The algorithm presented uses a local feature detector, speeded up robust features, to perform detection of brachytherapy seed 2D projections from images, allowing for robust seed identification. Initial results have been obtained with datasets of 30, 96 and 98 I-125 brachytherapy seeds implanted into a prostate gel phantom. It can detect 97% of seeds and correctly match 97% of seeds. The average overall computation time of 2.75 s per image and improved reconstruction accuracy of 22.87% for the 98 seed dataset was noted. Elimination processes for initial false positive detection removal have shown to be extremely effective, resulting in a 99.9% reduction of false positives, and when paired with automatic frame alignment and subtraction procedures allows for the effective removal of excess counts generated by previously implanted needles. The proposed algorithm will allow the BrachyView system to be used as a real-time intraoperative dosimetry tool for low dose rate prostate brachytherapy treatments.